The construction of the Social Right to education in Brazil: jesuits, sovereigns, liberals, conservatives, politicians and intellectuals - Daniel Dall'Igna Ecker; Neuza Maria de Fátima Guareschi; Lutiane de Lara; Marciana Zambillo (Universidade Federal de Santa Catarina, 2019)
This article analyzes the construction of the Social Right to education in Brazil, placing in the field of discussion the presence of certain social groups, jesuits, representatives of the Portuguese Crown, sovereigns, liberals, conservatives, politicians and intellectuals, in the naturalization of discourses on educating history of the country. Based on the historical perspective as an exercise in denaturalizing the present, was analyzed the Brazilian Federal Constitution of 1824; 1891; 1934; 1937; 1946; 1967; 1988; and the 2005 National Education Guidelines and Bases Law, aiming to understand how discourses about educating around the State sphere were produced. These discourses, through diverse social practices, served as justification for the creation of a series of public policies and programs, inserting the practice of educating as an important strategy of the Brazilian State for development of the nation and population management.